21 Initial clinical findings from a prospective rotational atherectomy registry. (5th October 2017) - Shand, J; Peace, A; Ramsewak, A; Sharma, D
Abstract : Rotational atherectomy (RA) of calcified coronary lesions has been used for almost 3 decades. Through plaque modification, it allows adequate stent expansion, theoretically reducing stent thrombosis and restenosis. UK data demonstrate increasing use of RA over recent years. Since January 2016, we have maintained a prospective registry of all RA cases and followed patients for major adverse cardiac events (MACE). During 2016, 753 PCI's were performed. RA was used in 36 cases (4.8%). Mean age was 75 years (+/- 9 years) and 72% were male. Patients presented electively in 42% of cases, stable acute coronary syndrome (ACS) in 42%, unstable ACS 14% and with ST elevation MI (STEMI) in 2% of cases. Mean Ejection fraction was 48% (+/- 10). Baseline mean Syntax Score was 22.3 (+/- 11.7).In total 34 cases (94%) were performed transradially. A temporary transvenous pacemaker was used in only 4 cases (11%). Primary target vessel for RA was the Left main stem (LMS) in 12 patients (33%), Left anterior descending 8 patients (22%), Circumflex 2 patients (6%) and Right coronary (RCA) in 13 patients (36%). Procedural success was achieved in 35 patients (94%). Maximum burr size was 1.75 mm with 86% of patients requiring only a 1.25 or 1.5 mm burr. In total, 34 patients (94%) had a mean 2.3 (+/- 1.3) drug eluting stents implanted. Mean total stent length was 63 mm (+/-27 mm). There was 1 periprocedural complication (distal wire perforation). During follow up, 4 patients (11%) had a MACE event (2 Non-ST elevation MI, 1 target lesion revascularization, 1 death). Complete revascularization (residual syntax score 0) was achieved in 40% of patients. Follow up MACE events were numerically higher in patients with incomplete revascularization (3 events vs. 1 event P = 0.619). This small series demonstrates the safety and efficacy of RA in contemporary PCI in a high-risk predominantly elderly cohort. Its use in patients presenting acutely including STEMI is more common than its use in the elective setting. The higher numeric MACE rate in patients with incomplete revascularization requires further exploration in a larger, ongoing registry.